2020
DOI: 10.1177/0271678x20918467
|View full text |Cite
|
Sign up to set email alerts
|

Brain deep medullary veins on 3-T MRI in a population-based cohort

Abstract: Our aim is to investigate whether vascular risk factors are associated with cerebral deep medullary veins (DMVs) and whether DMVs are associated with MRI markers of cerebral small vessel disease (CSVD) or risk of stroke. In a community-based cohort of 1056 participants (mean age 55.7 years), DMVs were identified on susceptibility-weighted imaging (SWI) and counted in periventricular regions. Neuroimaging markers including lacunes, whiter matter hyperintensity (WMH), microbleeds, enlarged perivascular space, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(59 citation statements)
references
References 13 publications
(15 reference statements)
4
52
3
Order By: Relevance
“…Owing to the difficulties in human pathological studies, the discontinuity or decreased number of DMVs visualised on SWI could be considered to be an imaging feature of venous collagenosis to assess the pathological changes in CSVD 2 31. Previous studies have suggested that a decreased number of DMVs was positively associated with age, whereas little is known about the potential mechanisms related to the cerebral small veins disease, or whether the number of DMVs is associated with inflammatory processes 1. Our results showed that high levels of systemic biomarkers, especially hsCRP, were negatively correlated with the number of DMVs, suggesting that an underlying mechanism mediated by inflammation was involved in the development of cerebral venule disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Owing to the difficulties in human pathological studies, the discontinuity or decreased number of DMVs visualised on SWI could be considered to be an imaging feature of venous collagenosis to assess the pathological changes in CSVD 2 31. Previous studies have suggested that a decreased number of DMVs was positively associated with age, whereas little is known about the potential mechanisms related to the cerebral small veins disease, or whether the number of DMVs is associated with inflammatory processes 1. Our results showed that high levels of systemic biomarkers, especially hsCRP, were negatively correlated with the number of DMVs, suggesting that an underlying mechanism mediated by inflammation was involved in the development of cerebral venule disease.…”
Section: Discussionmentioning
confidence: 99%
“…DMVs were visually counted in the periventricular WM of each hemisphere on reconstructed SWI. Details of the method are reported elsewhere 1. Briefly, a region of interest (ROI), 60×10 mm in size, was delineated in the periventricular WM between the frontal and occipital horn in each cerebral hemisphere.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 However, our previous study in a population-based cohort discovered that having fewer DMVs is not associated with conventional CSVD changes on MRI, such as lacunes, white matter hyperintensities (WMH), or cerebral microbleeds, but is strongly related to brain atrophy as indicated by the brain parenchymal fraction (BPF). 9 Thus, further research is in need on white matter (WM) microstructural alternation related to DMV. Meanwhile, changes in cerebral venules are possibly involved in different pathogenic mechanisms compared to those of other CSVD markers, and the potential role of neurodegenerative processes deserves more research attention.…”
Section: Introductionmentioning
confidence: 99%